2020
DOI: 10.1371/journal.pone.0230664
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of the African mound building termite, Macrotermes bellicosus workers to commercially formulated 2,4-D and atrazine caused high mortality and impaired locomotor response

Abstract: Recent empirical evidence suggests that herbicides have damaging effects on non-target organisms in both natural and semi-natural ecosystems. The African mound building termite, Macrotermes bellicosus, is an important beneficial insect that functions as an ecosystem engineer due to its role in the breakdown of dead and decaying materials. Here, we examined the effects of 2,4-D amine salt (2,4-D) and atrazine based herbicides viz. Vestamine ® and Ultrazine ® on the survival and locomotion response of M. bellico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
(75 reference statements)
2
6
0
Order By: Relevance
“…Also, reports of weed resistance to herbicides have resulted in the repeated application by farmers to eliminate weeds, consequently leading to harmful effects on non-target organisms (Duke, 2018). Despite the nutritional and ecological values of termites, there are limited studies on the adverse impact of herbicides on them (For exception, see Ejomah et al, 2020;Ekaye et al, 2022). Thus, in this study, we applied five concentrations of commercially manufactured glyphosate (Force up ® ) and paraquat (ParaQ ® ) on termites.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, reports of weed resistance to herbicides have resulted in the repeated application by farmers to eliminate weeds, consequently leading to harmful effects on non-target organisms (Duke, 2018). Despite the nutritional and ecological values of termites, there are limited studies on the adverse impact of herbicides on them (For exception, see Ejomah et al, 2020;Ekaye et al, 2022). Thus, in this study, we applied five concentrations of commercially manufactured glyphosate (Force up ® ) and paraquat (ParaQ ® ) on termites.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been reported that, exposure to glyphosate disrupts the gut microbiota and decreased cognitive behaviours in Apis mellifera (Herbert, 2014;Motta et al, 2018). Furthermore, Ejomah et al (2020) revealed that atrazine and 2,4-D resulted in 100% mortality in M. bellicosus while paraquat-induced low fertility in Anisopteromalus calandrae (Lacoume et al, 2009). All these buttress the deleterious impactz of herbicides on non-target organisms.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The mushroom exists in a symbiotic relationship with the termites, and this makes it difficult for domestication under laboratory conditions. Generally, termites are described as ecosystem engineers due to their activities in the soil which result in the availability of resources for other organisms [14]. However, they attack and destroy cocoa trees [15,16].…”
Section: Introductionmentioning
confidence: 99%